Tempos de execução da técnica de sons vibrantes e dados eletroglotográficos de idosas - Bárbara de Faria Morais Nogueira (2020)
Introduction: with the increase in the population's life expectancy, greater attention must be paid to elderly communication. Maintaining good voice quality allows the elderly to communicate more effectively, have greater self-esteem and remain invested in their social groups. The interest in addressing the situation of presbylarynx and presbyphonia is due to the fact that an elderly population has increased in recent years, generating the need to expand studies relating to this age group. Purpose: to analyze and compare the immediate vocal effects of the voiced vibrant sounds technique in the assessment of acoustic and auditory-perceptual measures of elderly women with and without self-perception of vocal alteration, and to present reference values for the fundamental frequency and closed phase quotient data extracted from the EGG in elderly women according to laryngeal diagnosis. Method: cross-sectional, clinical, quasi-experimental study, with a convenience sample composed of elderly women aged over 60 years. Two instruments were used to collect information: a questionnaire to collect sociodemographic data and the questionnaire for Tracking Vocal Changes in the Elderly – RAVI. The study took place in person at the Observatory of Functional Health in Speech Therapy – OSF with elderly women who attended or were in the vicinity of the Health Campus of the Federal University of Minas Gerais – UFMG in Belo Horizonte – MG. Data collection was carried out in four stages: questionnaire application, electroglottography, performance of the sonorous vibrating sound technique and laryngeal assessment. Data were analyzed using Statistical Package for Social Sciences – SPSS, version 21.0. Descriptive and data association analysis was performed. Descriptive analysis was performed using relative and absolute frequency distribution of categorical variables and numerical synthesis measures of quantitative variables. For the association analyses, Fisher's Exact, Pearson's Chi-Square, ANOVA and Kruskal-Wallis statistical tests were used, being considered as significant associations those with a value of p ≤ 0.05. For all tests, a significance level of 5% was considered. Results: presented in the form of two scientific articles, it was possible to verify in the first article that the effect of the vibrating sound technique was positive in the three periods evaluated in both groups. 53 elderly women aged between 60 and 70 years participated in this study. There was a predominance of moderate dysphonia in both groups, according to the experts' auditory-perceptual assessment. There was no statistically significant difference between the groups in the assessment of the auditory-perceptual analysis regarding the improvement, worsening and unaltered voice before and after the different times of technique execution. However, it was found that most of the elderly improved their voice, especially after one minute of performing the technique (56.6%). In the acoustic analysis there was statistical significance in the APQ parameters after performing the technique for one minute in the case group and in the control group there was no statistical significance. As for the second article, 70 elderly women participated, with a mean age of 69 years (SD=5.6). Most participants have high school (31.4%) and most are retired (90%). Regarding the laryngeal evaluation, 68.6% of the participants did not have laryngeal alterations, 8.6% had presbylarynx and 22.9% had signs of gastroesophageal reflux. There was no statistical significance when associating the laryngeal exam with the EGG variables and the elderly women's age. Conclusion: the effect of the sounded vibrant sounds technique was positive for both groups, but there was a reduction in improvement as the performance time increased. Elderly women present a high presence of voice alteration when considering the perceptive evaluation of the voice. Although the results indicate a predominance of improvement in the elderly women's voice after performing the technique in different execution times. The elderly women present mean F0 electroglottographic values of 187.27 Hz. The electroglottographic measurements of F0 and QC did not change with advancing age or with the laryngeal condition of the elderly women. The results of this study may help and guide the clinical practice of speech therapy in the elderly population, since there is a lack of studies on the themes investigated in this research